2019
DOI: 10.3390/insects10110377
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic Species Discrimination in Western Pine Beetle, Dendroctonus brevicomis LeConte (Curculionidae: Scolytinae), Based on Morphological Characters and Geometric Morphometrics

Abstract: The western pine beetle (WPB), Dendroctonus brevicomis LeConte, is a major mortality agent of pines in North America. A total of 706 adults of WPB from 81 geographical sites were analyzed with traditional and geometric morphometric methods to evaluate the variation of discrete and quantitative morphological characters with particular attention to the antenna, spermatheca, and seminal rod. Principal coordinates and canonical variate analyses supported three geographical groups in WPB: (1) West, from British Col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Morphometric analyses support that the shape of the seminal receptacle allows the recognition of distinct geographic groups in D. brevicomis, information that contributed to removing D. barberi Hopkins from synonymy (Valerio-Mendoza et al, 2019). In other congeners, this structure presents a species-specific shape, as is the case of D. approximatus-D. parallelocollis and D. mexicanus-D. vitei, whereas, in others such as D. frontalis and D. mesoamericanus, the shape of the spermatheca has only been partially differentiated (Armendáriz-Toledano et al, 2014).…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations
“…Morphometric analyses support that the shape of the seminal receptacle allows the recognition of distinct geographic groups in D. brevicomis, information that contributed to removing D. barberi Hopkins from synonymy (Valerio-Mendoza et al, 2019). In other congeners, this structure presents a species-specific shape, as is the case of D. approximatus-D. parallelocollis and D. mexicanus-D. vitei, whereas, in others such as D. frontalis and D. mesoamericanus, the shape of the spermatheca has only been partially differentiated (Armendáriz-Toledano et al, 2014).…”
Section: Introductionmentioning
confidence: 86%
“…The taxonomy of the genus Dendroctonus Erichson is traditionally based on external morphological attributes, such as the abundance, distribution, and size of cuticular ornamentation and pubescence on the different body parts (Hopkins, 1909;Wood, 1982). The use of these characteristics has shown that some of them are not useful to separate closely related species, because they present wide intraspecific geographic variation (Armendáriz-Toledano et al, 2014;Lanier et al, 1998;Valerio Mendoza et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dendroctonus barberi Hopkins occurs in eastern Nevad rado, Arizona, New Mexico, and Texas, U.S., and Mexico. We caution the barberi was synonymized with D. brevicomis in 1963 but was reinstated as a cies in 2019 based on differences in morphological characteristics, chemica other factors [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%